Modifikasi Pembuatan Tahu Dengan Penggunaan Lama Perendaman, Lama Penggilingan dan Penggunaan Suhu dalam Upaya Meningkatkan Kualitas Produk Tahu - Didik Iswadi (Program Studi Teknik Kimia, Universitas Pamulang, 2021)
In making tofu today, consuming energy for the tofu making process requires a large amount of energy. So that research must be able to choose the minimum energy use in the process of making tofu. Tofu has a short shelf life and quickly becomes rotten. The purpose of this study was to determine the best tofu making in terms of the use of variations in soaking time, boiling temperature and stirring time, knowing the best quality of tofu in terms of moisture content, protein content and texture of tofu products, knowing the value of tofu content from using variations in soaking time boiling temperature and stirring time. The quantitative method is taken from the analysis of water content, protein content, and tofu texture. The following is how to make tofu as follows, 1 kg of soybeans, washed sufficiently then soaked first, the soybeans are then milled with a special machine with 7 liters of raw water, heated, then stirred slowly, then take the clotted tofu with a scoop then put it in the mold and pressed or pressed, let stand until slightlycool, the last tofu is ready to be consumed. The result of modification test in making tofu that has the best value from the use of soaking time, grinding time, and temperature variation is sample 2 with a soaking time of 3 hours, 10 minutes of grinding time and a temperature variation of 80°C with a moisture content value of 82.17%, protein 11.61% and texture values of 6,44 N and 5,45 N.